Media Monitoring oleh Divisi Informasi di KJRI Johor Bahru - Audrey J. A. Manuputty; Aat Ruchiat Nugraha (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This study aims to analyze the media monitoring activities carried out by the Information Division at the Consulate General of the Republic of Indonesia (KJRI) in Johor Bahru. These activities are crucial for understanding how information circulating in the media influences the image and policies of the KJRI, as well as identifying issues relevant to Indonesian citizens in Malaysia. The study employs a descriptive qualitative method with data collection techniques including direct observation, in-depth interviews, and document analysis. The results of the study indicate that the Information Division at KJRI Johor Bahru has implemented various effective strategies in media monitoring, including the use of digital tools to monitor various media platforms. KJRI Johor Bahru conducts Media Monitoring, referred to as Weekly Reports (Lapming), in accordance with the definition of media monitoring activities by Friedel and Lukman (2020). Meanwhile, media tracking at KJRI Johor Bahru involves monitoring various credible online news sources, and media clipping at KJRI Johor Bahru aims to organize news collected from online sources and social media.